Analysis and experiment of the dynamic characteristics for root-soil system in the blueberry tree - Bao, Yudong; Liu, Yuying; Yuan, Naifeng (International Journal of Agricultural and Biological Engineering, 2024)
To solve the problem of soil loosening caused by whole plant vibration during the operation of a vibrating blueberry harvester, the force model of the blueberry tree containing root soil was established and analyzed. The main factors affecting the impact force of the shaker were the curvature of the shaker, the branch curvature, and the equivalent elastic modulus at the impact point. Through the analysis of the transfer law of vibration between the exciting force and the root-soil complex, it is concluded that the shear strength decreases with the decrease of the internal friction angle, resulting in loose soil and easy toppling of the fruit trees. Discrete element simulation was used to analyze the force of the blueberry model. The results showed that the lower the excitation height, the more drastic the fluctuation of the root-soil complex. In the range of excitation height from 200 mm to 500 mm, soil acceleration increased by 45.5% on average for every 150 mm decrease. From 200 mm to 50 mm, the average soil acceleration increased by 69.1%. Finally, through the field excitation sensor test, the sensor was buried in 200 mm, 100 mm, and 0 mm (that is, placed on the surface) of soil, and the exciting force was applied to blueberry branches at heights of 50 mm, 200 mm, 350 mm, and 500 mm, respectively, for four times, and then the soil acceleration was output. A total of 48 sets of experimental data were obtained. By combining the scattering data obtained from the experiment with the simulated curve, it can be analyzed that when the excitation heights were 50 mm and 500 mm, the soil fluctuation at the depth of 100 mm was close to the simulated average value. When the excitation heights were 200 mm and 350 mm, the fluctuation of surface soil with a depth of 0 mm was close to the simulated average value. When the excitation height was 500 mm, the root-soil complex fluctuated twice due to the obvious reciprocating swing of the fruit tree. Since very little vibration energy was consumed during transmission, the vibration was strongest in the surface soil. Soil with a depth of 200 mm was almost unaffected by the excitation force and excitation height because too much vibration energy was consumed during transmission. The results show that the established model and simulation scheme are reliable and can provide a theoretical basis for the optimization of the incentive parameters of blueberry fruit trees. Keywords: blueberry, fruit tree vibration, dynamic characteristics, root-soil system, experiment DOI: 10.25165/j.ijabe.20241706.8726 Citation: Bao Y D, Liu Y Y, Yuan N F. Analysis and experiment of the dynamic characteristics for root-soil system in the blueberry tree. Int J Agric & Biol Eng, 2024; 17(6): 59–65.